2020
DOI: 10.1001/jamainternmed.2020.2233
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak Investigation of COVID-19 Among Residents and Staff of an Independent and Assisted Living Community for Older Adults in Seattle, Washington

Abstract: IMPORTANCE Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused epidemic spread of coronavirus disease 2019 in the Seattle, Washington, metropolitan area, with morbidity and mortality concentrated among residents of skilled nursing facilities. The prevalence of COVID-19 among older adults in independent/assisted living is not understood.OBJECTIVES To conduct surveillance for SARS-CoV-2 and describe symptoms of COVID-19 among residents and staff of an independent/assisted living community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
134
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 14 publications
(27 reference statements)
7
134
0
2
Order By: Relevance
“…27 In addition, subcontracted staff may have less access to paid sick leave -a critical element in allowing staff to self-isolate when ill. All of this is in line with evidence that staff are the main vectors of SARS-CoV-2 transmission in LTC facilities. [28][29][30] We are unaware of data that allow for comparisons of wages and rates of multisite employment between Ontario and British Columbia.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, subcontracted staff may have less access to paid sick leave -a critical element in allowing staff to self-isolate when ill. All of this is in line with evidence that staff are the main vectors of SARS-CoV-2 transmission in LTC facilities. [28][29][30] We are unaware of data that allow for comparisons of wages and rates of multisite employment between Ontario and British Columbia.…”
Section: Discussionmentioning
confidence: 99%
“…In nine studies that reported on close contacts of infected individuals and aggregated data from clusters of both asymptomatic and symptomatic people with SARS-CoV-2 the summary estimate was 14% (95% CI 8%-23%, prediction interval 2%-53%) [36,47,60,62,66,72,105,108,111]. We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95].…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%
“…We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95]. The summary estimate of…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%
“…Each infection control strategy is limited in some aspect (22,(49)(50)(51)(52)(53). Symptom-based screening has very low sensitivity to detect infections early in the clinical course (when people are most infectious), and poor specificity (12)(13)(14)54). The impact of routine PCR testing is limited by imperfect PCR sensitivity (~75%), especially early in the infection course (19), as well as need for frequent testing and missing onset of infectiousness between testing periods.…”
Section: Discussionmentioning
confidence: 99%